Correlation between Clinical Characteristics and Chest Computed Tomography Findings of Pulmonary Cryptococcosis - Yamakawa, Hideaki; Yoshida, Masahiro; Yabe, Masami; Baba, Emiri; Okuda, Keitaro; Fujimoto, Shota; Katagi, Hiroaki; Ishikawa, Takeo; Takagi, Masamichi; Kuwano, Kazuyoshi (Pulmonary Medicine, 2015)
Objective. The aim of this study was to review HIV-negative patients with pulmonary cryptococcosis to analyze the correlations between clinical characteristics and chest computed tomography (CT) findings. Methods. We retrospectively analyzed medical records of 16 HIV-negative patients with pulmonary cryptococcosis diagnosed at our institution, and clinical characteristics of the patients with nodules or masses without ground-glass attenuation (GGA)/consolidation type were compared with those of patients with inclusive GGA or consolidation type. Results. Host status was immunocompromised (81.2%) in most of the patients, and 6 (37.5%) were asymptomatic. The most frequent radiologic abnormalities on chest CT scans were one or more nodules (87.5%), GGA (37.5%), and consolidations (18.8%). Most lesions were located in the lower lung. Levels of hemoglobin and platelets were significantly lower in patients with inclusive GGA or consolidation type. Although the differences were not significant, patients with inclusive GGA or consolidation type tended to have a C-reactive protein level of ≥1.0 mg/dL. Conclusion. If a patient with anemia and thrombocytopenia shows GGA or consolidation in the lung, pulmonary cryptococcosis should be given careful consideration.